Prognosis of ampullary cancer based on immunohistochemical type and expression of osteopontin - Zhang Wen-zhi; Dong Jia-hong; Zhao Xiang-qian; Liu Zhe (BMC, 2011)
Abstract Background Ampullary cancer (AC) was classified as pancreatobiliary, intestinal, or other subtype based on the expression of cytokeratin 7 (CK7) and cytokeratin 20 (CK20). We aimed to explore the association of AC subtype with patient prognosis. Methods The relationship of AC subtype and expression of Osteopontin (OPN) with the prognosis of 120 AC patients after pancreaticoduodenectomy was investigated. Results The patients had pancreatobiliary (CK7+/CK20-, n = 24, 20%), intestinal (CK7-/CK20+, n = 29, 24.2%) or other (CK7+/CK20+ or CK7-/CK20-, n = 67, 55.8%) subtypes of AC, and their median survival times were 23 ± 4.2, 38 ± 2.8 and 64 ± 16.8 months, respectively. The survival times of 64 OPN- patients (53.3%) and 56 OPN+ patients (46.7%) were 69 ± 18.4 and 36 ± 1.3 months, respectively. There was no significant effect of AC subtype on survival of OPN- patients. For OPN+ patients, those with pancreatobiliary AC had a shorter survival time (22 ± 6.6 months) than those with intestinal AC (37 ± 1.4 months, p = 0.041), and other AC subtype (36 ± 0.9 months, p = 0.010); intestinal and other AC subtypes had similar survival times. Conclusions The prognosis of AC patients can be estimated based on immunohistochemical classification and OPN status.